Thinking pattern of first grade students towards edentulous replacement - Eri H. Jubhari (Dental Journal (Majalah Kedokteran Gigi), 2007)
Many people ignore their oral hygiene and do not use denture after extraction. This may caused by their thinking pattern. Thinking pattern indicates the degree of comprehension to solve a problem. This research aims to find out the thinking pattern of first year students towards edentulous replacement. The questionnaire was filled in by students. The oral cavity state of students who have edentulous was inspected. The study finds that only 3 men and 27 women had edentulous, all of them did not use denture. However, more than 96% of the edentulous and not-edentulous groups said that edentulous need denture, due to aesthetic factor. The reasons for not using denture are, for example, not enough time, not disturbed by the absence of denture, and its cost. It can be concluded that the 2005 batch students of Faculty of Dentistry (FKG) UNHAS had shown a good understanding about edentulous replacement. Their views on the profits and detriments using denture are the main reasons to determine whether they will use denture.